Challenging the status quo: exploring the use of strategies from behavioral economics to shape children's menus in restaurants - Ferrante, Mackenzie Jayne, author; Bellows, Laura L., advisor; Johnson, Susan L., committee member; Slejko, Gina, committee member; Miller, Jeffrey, committee member (Colorado State University. Libraries, 2020)
Introduction: The poor diet quality of US children has been partially attributed to low fruit and vegetable intake and frequent consumption of restaurant food. Strategies from behavioral economics are acceptable to both parents and children and have increased children's orders of healthful foods in restaurants. However, there are still missing pieces related to parent acceptance and children's consumption of healthful foods. Therefore, the overarching goal of this dissertation is to investigate the feasibility and acceptability of using behavioral economic strategies in restaurants to alter children's consumption to be more healthful. This goal was addressed using two research objectives: 1a) To examine parent derived and stated preferences for selected attributes of children's restaurant menus, which included behavioral economic strategies, using a conjoint design and, 1b) to segment the participants by derived menu attribute preference to identify patterns in preference for individual menu attributes and overall stated and derived menu choice by participant characteristics, beliefs, health concern, and food practices. 2) To investigate whether altering the choice architecture of children's meals by restructuring the menu using optimal defaults and vice-virtue bundles, will impact ordering of side dishes and consumption of vegetable sides during a restaurant meal. Study 1: Eight children's menus were designed and integrated into a survey using conjoint design to gather parent appeal to various attributes and the overall menu. Parents of children (4-10 y; n=500) were recruited using Amazon's TurkPrime. A conjoint analysis was conducted to discern parent preference for each of the individual attributes. It revealed parents had a strong preference for choice on side dishes (β=0.73) and low-priced menus (β=0.51), and the weakest preference for inclusion of healthful entrees (β=0.04). Study 2: Families with 4-8 year old children were recruited to attend three dinner meals. Children's meals consisted of macaroni-and-cheese or chicken tenders and a default side dish [all carrots (150g; Menu-1), small fries (50g)/ large carrots (100g; Menu-2), and small carrots (50g)/ large fries (100g; Menu-3)]. Children could opt out of the default side. Foods offered to children were pre- and post-weighed to determine consumption. Descriptive statistics examined children's ordering behavior and consumption. Repeated measures ANOVA examined the effects on carrot consumption (g) and a paired samples t-test was conducted to test for differences in french fry consumption (g). A majority of children remained with the default side during each of the Menus: Menu 1, 90.2%; Menu 2, 97.6%; Menu 3, 87.8%. Significant differences occurred in children's french fry consumption, (t = -2.57, p = .014). No significant differences in children's carrot consumption occurred. Conclusions: Parents, like most consumers, value choice and options. The use of optimal, vice-virtue bundles was confirmed, showing that not only do children order more healthfully when they are in place, but that children will eat the healthful foods when present. Taken together, results from these two studies show that all stakeholders – children, parents, and restaurateurs - may be able to find a solution that offers both health and taste as a part of children's restaurant meals.